Single Index Model as Feasible Choice for Optimal Portfolio Formation - A.Ratna Sari Dewi; Nurdjanah Hamid; Julius Jilbert (International Journal of Economics, Business and Innovation Research, 2023)
In investing, investors are expected to have a portfolio or a combination of investment types owned by someone to obtain good results in determining the portfolio. There are many choices of investment combinations even unlimited. The combination of investments owned by investors must be able to provide profits and risks according to investors' preferences so that investors need to form an optimal portfolio. Investors are often confused about determining the optimal portfolio before investing. The single index model is a way that investors can use to see which investments can produce optimal portfolios because this model can calculate the returns and risks that can be obtained based on market movements.